Readings in Numanities (Numanities - Arts and Humanities in Progress,, 2018)
This unique book gathers articles from the numanistic perspective of multidisciplinarity and innovation, connected by three main theoretical interests or overarching themes: music, semiotics and translation. Offering an eclectic collection of innovative papers that address such topics as culture, musicology, art consumption, meaning, codes and national identities, to name a few, it has a broad appeal across the humanities and social sciences. The contributing authors draw on various schools and methodologies, including psychology, psychoanalysis, social semiotics, semiotic modelling, deconstruction and cultural analysis. By approaching established themes in new and challenging ways, this highly engaging book has the potential to advance the state of the art in various topics. It appeals to all scholars investigating cultural identity, linguistics and translation, music consumption, performance, semiotic theories and various intersections of these and related topics.